The impact of living in a fraternity home on the leadership identity of its members - Love, James Robert, II (Kansas State University, 2015)
Social organizations known as fraternities exist on many college campuses in the United States. Many of these organizations have a residential home either on the campus or off campus for the students known as a fraternity home. One of the values that many fraternities seek to ad-here to is found in the area of leadership (Long, 2012). Leadership has been studied for decades as has the social organizations known as fraternities. The outcomes of both of these areas of studies presented spirited and often complex discussion on how to define a) leadership and b) what is the role of the fraternity on the college campus. This qualitative study of 12 students focused on fraternity members who lived in a residential setting of a fraternity home. The purpose of this study was to understand what factors of the fraternity home experience have on one’s leadership identity and to explain how these factors can help guide college professionals in fostering in positive college student development. The researcher used two primary methods of data collection (a) focus groups and (b) in-depth individual semi-structured interviews. A case study research design was utilized to help understand the experiences that take place in the lives of the participants. The analysis of the data in this study helps explain how a college student living in a fraternity home takes on a leadership identity. Furthermore, this study pointed to six themes that emerged to help inform how a residential living setting of a fraternity home shapes the leadership identity of the students. Multiple support systems allow for students to have values tested and reinforced though a fraternity home experience. Diversity of other viewpoints are present in a fraternity and allow for students to see differing perspectives. Older fraternity brothers have a positive influence on younger members in terms of self-confidence, mentoring, and other areas. Positional leadership roles of the fraternity allow students to engage with managing conflict and interacting with adult advisors and mentors. Brotherhood events provide students the opportunity develop relationships and interpersonal skills. Formal chapter meetings allow a venue for students to engage with each other in a manner that produces improved communication skills and critical thinking. Student affairs professionals and leadership educators working with students including but not limited to Greek organizations can take the findings of the study to assist them in their work. A leadership identity is being formed through a fraternity home setting as evidence of this study. Leadership educators can use this study to help their thoughts on how college students, especially fraternity members, view and exercise leadership. This study also presented areas for future research based on the information that was gained from the participants. Colleges continue to need contemporary studies to help them in working enhance the academic and social experience. The information provided in this study can be a catalyst for helping the understanding of leadership and for student development.
Keywords: Leadership; Leadership identity; Fraternity; Fraternity home; Greek life; Greek; Education, General (0515)